Numerical prediction of surface morphology and roughness in rotary ultrasonic face grinding SiO2f/SiO2 composite - Longxu Yao; Zhanqiang Liu; Qinghua Song; Bing Wang; Yukui Cai; Jinfu Zhao (Journal of Materials Research and Technology, 2023)
The SiO2f/SiO2 ceramic matrix composite has been applied to fabricate high-performance radar radome because of its good wave transmission and mechanical property. The machined surface morphology and roughness of SiO2f/SiO2 ceramic matrix composite have an important impact on the service performance of radome products. This paper presented a numerical model to predict surface morphology for grinding of SiO2f/SiO2 composite. The prediction model was based on finite element method (FEM). Both conventional face grinding (CFG) and rotary ultrasonic face grinding (RUFG) of SiO2f/SiO2 composite were FEM simulated by integrating the microstructure of SiO2f/SiO2, the constitutive as well as failure mechanism of fiber/matrix, and the coupling grinding effect of multiple abrasive grits. The machined surface morphology was predicted by extracting node coordinates on simulated ground surface. The numerical prediction results were quantitatively validated using experimental results of ground surface roughness Sa. The application of the proposed prediction model not only elucidated the influence law of fiber orientations and machining parameters on ground surface quality but also revealed the different shear failure modes of SiO2 fiber during grinding process. The ground surface of SiO2f/SiO2 was deteriorated by uncut-off debonding fibers and fiber peeling pits. Ultrasonic-assisted vibration was beneficial to improve ground surface quality by force reduction and hammering effect caused by intermittent machining. However, the key prerequisite for the ultrasonic hammering effect to exert its process advantage was that the ultrasonic hammering energy could effectively fracture fibers on the ground surface rather than being absorbed by crack propagation at the fiber–matrix interface.